Traps: a low cost IPM tool for pest monitoring and management in groundnut ecosystem: Traps: a low cost IPM tool for pest monitoring and management in groundnut ecosystem - G N SHREEVANI,; S SREEDEVI CHAVAN,; B RAJANNA, (Journal of Oilseeds Research, 2020)
Monitoring of insect pests in groundnut ecosystem using traps (pheromone and yellow sticky traps) was carriedout at Main Agricultural Research Station, University of Agricultural Sciences, Raichur, Karnataka for a period ofseven years (2012-2018). The pooled data of the trap catches showed that highest numbers of Spodoptera litura were caught during the 45th standard meteorological week (79.80/trap), while the leafhopper, thrips and leaf miner catches recorded highest numbers during 43rd (7.2/trap), 40th (7.6/trap) and 38th (4.2/trap) standard meteorological week, respectively.